Pengaruh Model Pembelajaran Probing-Prompting Berbantuan Lembar Kerja Berstruktur Terhadap Hasil Belajar Siswa - Rini Lestari; Diana Kholilah (Gravity Journal, 2023)
This research was conducted because the learning process uses lecture methods that make the learning process monotonous, the delivery of material unilaterally and passively positioning students, and students cannot express their abilities so that the abilities that exist in students are not developing optimally. The purpose of this study was to determine the learning outcomes by applying a probing- prompting learning model with the help of structured worksheets on straight motion material in SMA Negeri 7 Lhokseumawe. This type of research is a pre-experiment conducted in class X MIPA 1 of SMA Negeri 7 Lhokseumawe, with a total of 21 students. The sampling process is done by purposive sampling. Data collection techniques using learning outcomes tests. The number of valid questions is 25 questions with an average value of 0.76, the reliability value is 0.87. Data analysis techniques on learning achievement tests used paired sample t-test. The results of the paired sample t- test pretest and posttest test obtained significance = 0,000, which means a significance value of 0,000 0.05 then Ha is accepted and Ho is rejected. The data shows that there is an effect of the Probing-prompting learning model with the help of structured worksheets on student learning outcomes on straight motion material at SMA Negeri 7 Lhokseumawe.